2016
DOI: 10.5603/fm.a2015.0078
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes of nasal cavity and conchae volumes and volume fractions in children: a stereological study

Abstract: (Folia Morphol 2016; 75, 1: 38-47)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…The mean volumes of structures measured in mentioned studies are given in Table 5 as a comparison of literature. Similarly as Emirzeoglu et al 6 and Ertekin et al, 7 we reported that a significant difference between male and female subjects in the NC measurements. We detected, as in these 2 studies, that the males' NC volumes and other structures' volumes in NC were greater than those in females.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The mean volumes of structures measured in mentioned studies are given in Table 5 as a comparison of literature. Similarly as Emirzeoglu et al 6 and Ertekin et al, 7 we reported that a significant difference between male and female subjects in the NC measurements. We detected, as in these 2 studies, that the males' NC volumes and other structures' volumes in NC were greater than those in females.…”
Section: Discussionsupporting
confidence: 85%
“…This study is a reference study in Turkish population, where wide-scale volumetric calculations are made using stereological method. Also, the volume of the nasal septum was evaluated in this study, unlike in the study conducted by Emirzeoğlu et al 6 Ertekin et al 7 and Emirzeoğlu et al 6 used CT images with a cross-sectional thickness of 0.6 mm and 3 mm, respectively. Unlike these 2 studies, we examined a 0.4 mm slice of thickness on CBCT images.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations